Role of ARHGEF3 as a GEF and mTORC2 Regulator - Khaliq, Sana Abdul; Umair, Zobia; Yoon, Mee-Sup (Frontiers in Cell and Developmental Biology, 2022)
Guanine nucleotide exchange factors (GEFs) activate GTPases by stimulating the release of guanosine diphosphate to permit the binding of guanosine triphosphate. ARHGEF3 or XPLN (exchange factor found in platelets, leukemic, and neuronal tissues) is a selective guanine nucleotide exchange factor for Rho GTPases (RhoGEFs) that activates RhoA and RhoB but not RhoC, RhoG, Rac1, or Cdc42. ARHGEF3 contains the diffuse B-cell lymphoma homology and pleckstrin homology domains but lacks similarity with other known functional domains. ARHGEF3 also binds the mammalian target of rapamycin complex 2 (mTORC2) and subsequently inhibits mTORC2 and Akt. In vivo investigation has also indicated the communication between ARHGEF3 and autophagy-related muscle pathologies. Moreover, studies on genetic variation in ARHGEF3 and genome-wide association studies have predicted exciting novel roles of ARHGEF3 in controlling bone mineral density, platelet formation and differentiation, and Hirschsprung disease. In conclusion, we hypothesized that additional biochemical and functional studies are required to elucidate the detailed mechanism of ARHGEF3-related pathologies and therapeutics.